„Polski” Rilke - Kałążny, Jerzy (Poznańskie Studia Polonistyczne. Seria Literacka, 2012)
The publication of Katarzyna Kuczyńska-Koschany’s book Rycerz i Śmierć. O Elegiach duinejskich Rainera Marii Rilkego fills the large gap in Polish research on Rilke as it is the first monographic study of the Duino elegies. The author of the book interprets individual elegies and Atical sensibility. Simultaneously, the author supports her analysis with the theoretical foundations created by acclaimed and reputed German researchers of Rilke’s literary output such as Käte Hamburger, Beda Allemann, Manfred Engel and Jacob Steiner, among others. In her considerations, the author also refers to Polish translation of the elegies, notably those made by Mieczysław Jastrun and Adam Pomorski, also providing their critical interpretation.